Increased levels of serum IgA as IgA1 monomers in ankylosing spondylitis. Issue 6 (June 1992) - Hocini, H; Iscaki, S; Benlahrache, C; Vitalis, L; Chevalier, X; Larget-Piet, B; Bouvet, J P
Abstract : The various subsets of serum IgA were determined in 43 patients with ankylosing spondylitis to investigate the putative mucosal origin of increased IgA concentrations in this disease. Total IgA was shown to be increased and weakly correlated with the erythrocyte sedimentation rate (ESR). In contrast, although the mean concentration (but not the median) of secretory IgA (SIgA) was slightly increased, no correlation was found with total IgA nor the ESR. Moreover, molecular sieving of nine serum samples selected for their high concentrations of total IgA, and absorption with insoluble jacalin showed these immunoglobulins to be essentially monomers of the IgA1 subclass. These results are consistent with a non-secretory origin of the increase of serum IgA, which must be ascribed to the central immune system.